2015
DOI: 10.1111/bju.13248
|View full text |Cite
|
Sign up to set email alerts
|

Association between very small tumour size and increased cancer‐specific mortality after radical prostatectomy in lymph node‐positive prostate cancer

Abstract: ObjectiveTo determine whether very small prostate cancers present in patients who also have lymph node (LN) metastases represent a particularly aggressive disease variant compared with larger LN-positive tumours. Patients and MethodsWe identified 37 501 patients diagnosed with prostate cancer between 1988 and 2001 treated with radical prostatectomy within the Surveillance, Epidemiology, and End Results database. The primary study variables were tumour size by largest dimension (stratified into: (i) microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As vinayak et al. ( 27 ) had same view, they found patients who had LNM in very small prostate cancers presented a particularly aggressive disease variant compared with larger tumors. These small tumors may represent higher mutation rates and thus evade the body’s immune surveillance and anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As vinayak et al. ( 27 ) had same view, they found patients who had LNM in very small prostate cancers presented a particularly aggressive disease variant compared with larger tumors. These small tumors may represent higher mutation rates and thus evade the body’s immune surveillance and anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 72%
“…These studies may support our hypothesis that smaller tumors in EC patients with LNM may represent greater biological aggressiveness and earlier acquisition of genetic changes that promote tumor cell spread to regional or distant sites. As vinayak et al (27) had same view, they found patients who had LNM in very small prostate cancers presented a particularly aggressive disease variant compared with larger tumors. These small tumors may represent higher mutation rates and thus evade the body's immune surveillance and antitumor immune response.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In 2011, an impressive research found that very small tumors would present aggressive biology when involved in node-positive breast cancer (16). Then, similar findings were demonstrated in colon and prostate cancer (17,18). These findings challenged the traditional view that cancer gains the ability to metastasize as it grows to a larger size (9).…”
Section: Discussionmentioning
confidence: 98%
“…Although the traditional view of malignant progression is that cancer gains metastatic ability through an accumulation of mutations as they grow to a large size, recent studies have suggested that for some tumors, the acquisition of metastatic potential may occur early in cancer development, even in the absence of detectable primary tumors. It was previously reported that very small tumor size with intensive lymph node involvement was related to worse survival in breast cancer [ 8 ], colon cancer [ 9 ] and prostate cancer [ 10 ]. In melanoma, Sanjay et al [ 5 ] discovered that in LN positive melanomas, patients with tumor thickness ≤0.50 mm had higher mortality than those with tumor thickness 0.51–1.00 mm or 1.01–2.00 mm.…”
Section: Discussionmentioning
confidence: 99%